تحليل تطبيق طريقة التعلم التعاوني في تعليم مهارة القراءة لرسائل الطلبة بقسم تعليم اللغة العربية سنة ۲۰۱۷-۲۰۱۹ - Ananda, Ribqa; Ninoersy, Tarmizi; Fajriah, Fajriah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
To achieve the learning objective teacher use various methods in learning. One of wich is a group learning method. The purpose of this study is to determine the effevtivenes of the application of group learning method in learning reading skill and to determine students responses to the application of group learning method in learning reading skill. The method used in this research is the analysis method with a content analysis model. Researcher analyzed the thesis of Arabic Language Education Students relating to the application of group learning method in reading skill. The method used to collect data is the document method. The result of this study explain that applying the group learning method to reading skill is effective in increasing student ability to read. And student responses to the application of group learning method in learning reading skill are very good for increasing student motivation in learning and increasing student activity in teaching and learning. And makes it easier for student to understand the content of the subject.